2022
DOI: 10.3390/ijms23042152
|View full text |Cite
|
Sign up to set email alerts
|

Opinion: On the Way towards the New Paradigm of Atherosclerosis

Abstract: Atherosclerosis is a multicausal disease characterized by the formation of cholesterol-containing plaque in the pronounced intima nearest to the heart’s elastic-type arteries that have high levels of blood circulation. Plaques are formed due to arterial pressure-induced damage to the endothelium in areas of turbulent blood flow. It is found in the majority of the Western population, including young people. This denies the monogenic mechanism of atherogenesis. In 1988, Orekhov et al. and Kawai et al. discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 100 publications
0
22
0
1
Order By: Relevance
“…Earlier, we showed that in newborn rats, when the GC is overloaded, the chylomicrons were delayed in the post-Golgi compartment positive for LAMP2, a marker of lysosomes and late endosomes [ 80 ]. Since we were familiar with the contradiction of desialilyation of modified LDLs [ 5 ], we checked whether in adult animals, after the enterocyte overloading with lipids, post-Golgi carriers pass through LAMP2-positive compartments. To test the hypothesis that desialylation of ApoB and superficial lipids of chylomicrons may take place due to alterations of post-Golgi transport, we studied enterocytes of the small intestine taken from rats that were fed with a large amount of lipids into the stomach.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier, we showed that in newborn rats, when the GC is overloaded, the chylomicrons were delayed in the post-Golgi compartment positive for LAMP2, a marker of lysosomes and late endosomes [ 80 ]. Since we were familiar with the contradiction of desialilyation of modified LDLs [ 5 ], we checked whether in adult animals, after the enterocyte overloading with lipids, post-Golgi carriers pass through LAMP2-positive compartments. To test the hypothesis that desialylation of ApoB and superficial lipids of chylomicrons may take place due to alterations of post-Golgi transport, we studied enterocytes of the small intestine taken from rats that were fed with a large amount of lipids into the stomach.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a rather high incidence of atherosclerosis in vegans (although to a lesser extent than in meat eaters) suggests that atherogenesis is not limited to increased cholesterol intake alone. Moreover, many people consume eggs and meat in high concentrations, and they do not develop atherosclerosis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations